2015
DOI: 10.4014/jmb.1409.09012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Hexane Fraction from Myagropsis myagroides on Pancreatic ��-Amylase In Vitro

Abstract: A Myagropsis myagroides (Mm) methanol extract showed α-amylase inhibitory activity of 13% at a concentration of 5 mg/ml. Results showed that the hexane fraction from the Mm methanol extract exhibited α-amylase inhibitory activity with an IC50 value of 4.24 mg/ml. The hexane fraction was separated using silica-gel column chromatography, and six subfractions were obtained. The fraction eluted with CHCl3:MeOH = 50:1 showed the highest α-amylase inhibitory activity with an IC50 value of 0.72 mg/ml. This fraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Debasis et al (2013) had observed the highest α-amylase and α-glucosidase inhibitory activity in the n-hexane fraction of sepal of Salmalia malabarica [31]. The n-hexane fraction of Myagropsis myagroides showed significant amylase inhibition [32]. Saleh et al (2013) observed significant α-glucosidase and α-amylase inhibitory in the n-hexane fractions of ten plant extracts traditionally used in Iran for diabetes [33,34].…”
Section: α-Amylase and α-Glucosidase Inhibition Studiesmentioning
confidence: 99%
“…Debasis et al (2013) had observed the highest α-amylase and α-glucosidase inhibitory activity in the n-hexane fraction of sepal of Salmalia malabarica [31]. The n-hexane fraction of Myagropsis myagroides showed significant amylase inhibition [32]. Saleh et al (2013) observed significant α-glucosidase and α-amylase inhibitory in the n-hexane fractions of ten plant extracts traditionally used in Iran for diabetes [33,34].…”
Section: α-Amylase and α-Glucosidase Inhibition Studiesmentioning
confidence: 99%
“…For example SCA-C contains a 9′-hydroxyl group with R-configuration in the side-chain, while SCA-F has a methoxy group at C-9′ and a hydroxyl group with Rconfiguration at C-10′ (extensively reviewed in Birringer et al, 2018). SCAs have been reported to exhibit various biological activities, including anti-oxidative (Lim et al, 2019) (SCA-G), anti-osteoclastogenic (Yoon et al, 2012b;Yoon et al, 2013) (SCA-G), anti-inflammatory (Yoon et al, 2012a;Lee et al, 2013;Heo et al, 2014) (SCA-G and SCA-D), as well as antidiabetic (Pak et al, 2015) (SCA-I) ones. To the best of our knowledge, metabolism of sargachromanols in humans or animals has not been investigated.…”
Section: Sargachromanolsmentioning
confidence: 99%
“…Sagachromanols (1~16) were isolated from the brown alga Sargassum siliquastrum as novel bioactive substances [12] . In a previous study [13] , sargachromanol I was isolated from M. myagroides, which inhibited amylase activity. In this study, in vitro anticollagenase and free radical scavenging activities of M. myagroides extracts were investigated, particularly the hexane fraction, and the isolated active compound sargachromanol I.…”
mentioning
confidence: 98%